Increasing Public Knowledge About Sedentary Activities Through Counseling at SMPIT Zain Al-Muttaqin, Palembang, Indonesia - Mariana; Dwi Handayani; Muhammad Aziz; Agita Diora Fitri; Riafatiulfi Ilyasa; Nabila Istighfarin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Sedentary activities are activities that require very low energy expenditure, such as sitting or lying down while watching television, playing electronic games, and reading which can have negative health effects. This study aimed to describe the comparison of participants' knowledge before and after counseling about sedentary activities. Methods: An experimental study with one group pre-test and post-test design was conducted on 22 students of SMPIT Zain Al-Muttaqin Palembang. Data were analyzed using the Wilcoxon test. Results: There were 63.6% of participants' knowledge was in the poor category before counseling, and after counseling, the participant's knowledge increased by 59.1% in the good category. From the Wilcoxon test analysis, the result is the value of Sig. (2-tailed) of 0.000 < 0.05. Conclusion: Student knowledge is increased about activities sedentary after counseling, and there is a significant difference in the results of sedentary lifestyle counseling based on data pre-test and post-test (P<0,05).